Biofuel technologies : recent developments - Gupta, Vijai Kumar; Tuohy, Maria G. (Springer, 2013)
This book provides recent updates on biofuels and bioenergy. Topics include biomethane production, feedstock production, biomass pre-treatment, enzyme hydrolysis, genetic manipulation in microbial cells, and economic process technology of biofuels residues